Nutrient stock in soil and trees in a secondary forest provided for shifting cultivation - Trüby, Peter; Vogel, Hamilton Luiz Munari; Schumacher, Mauro Valdir (Revista Ecologia e Nutrição Florestal - ENFLO, 2014)
In South Brazil slash and burn plays a major role for great number of small farmers. However, there is almost no fertilization with mineral fertilizers to compensate the nutrient loss. The aim was to assess the ecological risks. An inventory of the nutrients in the biomass and the soil was done and the potential loss by burning was calculated. Nutrient input by precipitation was measured weekly to estimate the compensation of nutrient losses by atmospheric input. The nutrient status of the ecosystem was on a high level. It was far away from the status of natural rainforests on Ferralsols in the humid tropics. Assessing the ecological risk by a worst case scenario a twofold repetition of slash and burn would empty almost the total stock of exchangeable Mg in the soil. However, considering the real situation after practicing slash and burn for more than 100 years there is no indication that this is real scenario. Obviously the nutrient loss is smaller and a recuperation of the ecosystem occurs by atmospheric input and weathering of primary silicates. For to maintain sustainability it is recommended to provide a recovery time of at least some decades. Nutrient loss could be strongly reduced if branches would be left in the system and biomass extraction was restricted to stemwood. It would be helpful if magnesium loss could be partly compensated through liming or magnesium fertilizers DOI: http://dx.doi.org/10.13086/2316-980x.v01n01a04